Nonpharmacological pain management methods used by post-operative patients: A cross-sectional study - Senay Karadag Arli (Journal of Perioperative Nursing)
Objectives: Surgical patients use many nonpharmacological methods to manage pain after surgery. Knowing these methods and relieving the patient’s surgical pain will increase the quality of care. This study aims to examine the nonpharmacological pain management methods used by surgical patients and identify significant relationships between gender and participants’ clinical characteristics.